Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors